Accessing the Edge: Delay Evaluation to Distributed Edge Services in a City-Level 5G Network - Frei, Matthias; Karbownik, Piotr; German, Reinhard; Djanatliev, Anatoli (2024 IEEE International Conference on Cloud Engineering (IC2E), 2024)
Cloud combined with Multi-Access Edge Computing (MEC) empowers service creators and application developers with promising architectural design and communication performance improvements. In fifth generation (5G) and in 6G cellular networks, MEC gains more importance as a service platform to enable new applications. However, as of today, the availability of MEC resources in public networks is still low, thus not much communication performance measurement data exists. In this work, we use our private, city-level 5 G test bed, to evaluate the end-to-end communication performance to different edge and cloud endpoints through realistic outdoor field tests. Multiple topological locations of the edge service are evaluated, the network is operated in stand-alone (SA) and non-standalone (NSA) modes, and two-way as well as one-way latency measurements with multiple traffic patterns are performed. The measurements are executed in different environmental settings: fixed position and drive tests, including 5 G cell hand-overs. The results not only demonstrate the performance benefits gained from MEC resources, but also show the impact of the communication system and user mobility to Quality of Service (QoS) parameters. Especially for different traffic patterns and for the performance during our drive tests, our results show the time overhead required for exchanging data, which may be challenging for service lookups or delay-constrained applications.<br
Keywords: edge computing; cloud; MEC; 5G; QoS; latency; RTT; OWD; PDV; performance; field test